Sequencing of Chloroplast Genome Using Whole Cellular DNA and Solexa Sequencing Technology - Wu, Jian; Liu, Bo; Cheng, Feng; Ramchiary, Nirala; Choi, Su-Ryun; Lim, Yong Pyo; Wang, Xiaowu (Frontiers in Plant Science, 2012)
Sequencing of the chloroplast genome using traditional sequencing methods has been difficult because of its size (>120 kb) and the complicated procedures required to prepare templates. To explore the feasibility of sequencing the chloroplast genome using DNA extracted from whole cells and Solexa sequencing technology, we sequenced whole cellular DNA isolated from leaves of three Brassica rapa accessions with one lane per accession. In total, 246 Mb, 362Mb, 361 Mb sequence data were generated for the three accessions Chiifu-401-42, Z16 and FT, respectively. Microreads were assembled by reference-guided assembly using the cpDNA sequences of B. rapa, Arabidopsis thaliana, and Nicotiana tabacum. We achieved coverage of more than 99.96% of the cp genome in the three tested accessions using the B. rapa sequence as the reference. When A. thaliana or N. tabacum sequences were used as references, 99.7–99.8% or 95.5–99.7% of the B. rapa chloroplast genome was covered, respectively. These results demonstrated that sequencing of whole cellular DNA isolated from young leaves using the Illumina Genome Analyzer is an efficient method for high-throughput sequencing of chloroplast genome.